2020
DOI: 10.1017/jfm.2020.773
|View full text |Cite
|
Sign up to set email alerts
|

Regimes of wettability-dependent and wettability-independent bouncing of a drop on a solid surface

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
(244 reference statements)
1
7
0
Order By: Relevance
“…In a recent report, Zhang et al, also showed interfacial perturbations at the liquid–air interface induced by the top surface collapse, which purportedly triggered a thin film instability when the wavelength of the perturbing capillary waves exceeded a critical value . Similar fluctuations in the liquid–air interface induced by the strong oscillation on the upper surface of the drop was further probed via simulation by Sharma and Dixit . Noting the pronounced perturbations of the drop-air interface during both the spreading and retraction phases, we attribute the contact bouncing mechanism to be strongly tied to the bottom surface undulations during rebound which is aided by the liquid film deformation.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In a recent report, Zhang et al, also showed interfacial perturbations at the liquid–air interface induced by the top surface collapse, which purportedly triggered a thin film instability when the wavelength of the perturbing capillary waves exceeded a critical value . Similar fluctuations in the liquid–air interface induced by the strong oscillation on the upper surface of the drop was further probed via simulation by Sharma and Dixit . Noting the pronounced perturbations of the drop-air interface during both the spreading and retraction phases, we attribute the contact bouncing mechanism to be strongly tied to the bottom surface undulations during rebound which is aided by the liquid film deformation.…”
Section: Discussionsupporting
confidence: 61%
“…Drop oscillation dynamics in-flight has been shown to be important in recent works where the oscillation decay is a strong function of the We and Re d .For instance, small undulations on the lower surface of a falling drop occurs when Re d ≫ We. 60 The oscillation decay time for an in-flight drop is given by τ decay = ρ(D 0 /2) 2 /(5 μ) ≈248 ms, reported earlier by Lamb. 61 However, the longest flight time scale t f = U 0 /g ≈ 60 ms, given by the largest impact velocity in our experiment, which is at least four times smaller than the oscillation decay time.…”
Section: ■ Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…One basic question is whether the drop liquid is in direct contact with the solid surface at the moment of determining the contact angle [35]. It was found that droplets bounce off of a surface if the surface happens to be nonwetted by the droplet phase, however, it has also been reported that there exists a fluid cushion which appears also when the surface is wetted by the droplet [36]. This is confirmed by Fig.…”
Section: Introductionmentioning
confidence: 79%